Learning English vocabulary from word cards: A research synthesis - Lei, Yuanying; Reynolds, Barry Lee (Frontiers in Psychology, 2022)
Researchers’ interest in the learning of vocabulary from word cards has grown alongside the increasing number of studies published on this topic. While meta-analyses or systematic reviews have been previously performed, the types of word cards investigated, and the number of word card studies analyzed were limited. To address these issues, a research synthesis was conducted to provide an inclusive and comprehensive picture of how the use of word cards by learners results in vocabulary learning. A search of the Web of Science and Scopus databases resulted in 803 potential studies, of which 32 aligned with the inclusion criteria. Coding of these studies based on an extensive coding scheme found most studies assessed receptive vocabulary knowledge more often than productive vocabulary knowledge, and knowledge of vocabulary form and meaning were assessed more often than knowledge of vocabulary use. Results of effect size plots showed that more of the reviewed studies showed larger effects for the use of paper word cards than digital word cards, and for the use of ready-made word cards than self-constructed word cards. Results also indicated more studies showed larger effects for using word cards in an intentional learning condition compared with an incidental learning condition, and for using word cards in a massed learning condition compared with a spaced learning condition. Although a correlation was found between time spent using word cards and vocabulary learning outcomes, this correlation was not statistically significant. Learners that were more proficient in English learned more words from using word cards than those less proficient. These results suggest that future researchers should report learner proficiency, adopt reliable tests to assess vocabulary learning outcomes, compare the effectiveness of ready-made word cards and self-constructed word cards, and investigate the learning of different aspects of word knowledge. Teachers should provide learners guidance in how to use word cards and target word selection for self-construction of word cards. In addition, teachers should encourage learners to create word cards for incidentally encountered unknown words and use massed learning when initially working with these new words before using spaced learning for later retrieval practice.